Unraveling sustainable household well-being in disaster resettled areas: multidimensional measurement and determinants - Zhu, Qiantao; Luo, Xinhong; Zhao, Shanshan; Duan, Yuting; Liu, Wei (Frontiers in Sustainable Food Systems, 2025)
To reduce the threat of natural disasters and promote human well-being, Shaanxi Province, China, relocated 2.4 million people from three cities in the south in 2011. As the largest disaster resettlement project ever implemented in China, its scale, investment, extent, and impact deserve the continuous attention of policy researchers and practitioners. The impact of this project on rural-scale livelihoods and well-being especially needs more empirical evidence and comprehensive assessment. This article refers to the MA (Millennium Ecosystem Assessment) indicator system to measure the sustainable household well-being (SHWB) of disaster resettlement households using survey data from Southern Shaanxi, China. To explore the determinants of the SHWB of disaster resettlement households, this paper employs a quantile regression model for analysis. The results show that, compared to voluntary relocation households, long-distance relocation households, and medium or short-term relocation households, the SHWB of involuntary relocation households, short-distance relocation households, and long-term relocation households, respectively, is not only significantly higher, but also fluctuates greatly. In addition, voluntary relocation has a significant negative impact on SHWB, while short-distance relocation and medium and long-term relocation have a significant positive impact on SHWB. Furthermore, the education level of household members demonstrates a significant positive impact on SHWB. These findings have extensive implications for disaster resettlement and management in China and other developing nations. They are critical to improving the quality of farmers’ livelihoods and promoting sustainable well-being for rural households.